Values of Character Education in Nurcholish Madjid's Biography and Their Relevance to Akidah Akhlak Subjects (Study Cak Nur's book, Sang Guru Bangsa by Muhammad Wahyuni Nafis) - Nasir, Muhammad; Khalilurrahman (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
This study aims to determine the values of character education contained in Nurcholish Madjid's biography entitled Cak Nur Sang Guru Bangsa by Muhammad Wahyuni Nafis and its relevance to the material on familiarizing commendable morals in the Akidah Akhlak class VIII year 2020 subject at Madrasah Tsanawiyyah. This research is useful for enriching scientific treasures for researchers of history and Islamic thought and for reference in the world of Islamic Religious Education. This was library research, or literature study in the sense that all the data comes from written materials, namely the author studies and examines library materials, especially regarding issues of character education values and moral principles. This research uses content analysis and descriptive method. Content analysis is used to reveal, understand, and capture the contents of the writing, while the descriptive method is used to discuss the research object as it is according to the data obtained. This study found the values of character education in Cak Nur Sang Guru Bangsa's biography, namely: religion, tolerance, discipline, hard work, creative, democratic, peace-loving, fond of reading, social care, and responsibility. The relevance of Cak Nur's book Sang Guru Bangsa with the subjects of aqidah morals includes: Endeavor, trust, gratitude, patience, qana'ah, husnuzan, tawadu, tasamuh, and ta'awun.